Partisipasi Masyarakat Dalam Implementasi Kebijakan Desentralisasi Administratif di Sub Distrik Pante-Makassar - Agustinho Elu; Teguh Yuwono; Tri Yuningsih; Teuku Afrizal (Mahesa Research Center, 2021)
This research focuses on the Implementation of Administrative Decentralization Policy in the Pante Makassar Sub-District, Oe-Cusse Ambeno Special Administrative Region. This study aims to analyze the implementation of the administrative decentralization policy in the Pante-Makassar sub-district, the Special Administrative Region of Oe-Cusse Ambeno, Timor Leste and the factors that influence the implementation of the administrative decentralization policy. The approach used by the researcher is to use a qualitative approach or method with the research location in the Pante Makassar Sub-District Government, Oe-Cusse Ambeno Special Administrative Region. Primary data is obtained by conducting direct research on the object of research using observation, interview or interview data collection techniques. Secondary data is obtained through literature study to collect data through books, regulations, and documents that are relevant to the research. The respondents of this study were the entire community of the Pante Makassar District as the target of the implementation of Administrative decentralization. Accidental sampling technique. The results showed that the implementation of the Administrative Decentralization Policy showed that the people of the Pante Makassar Sub-district participated in decision making. The community also participates in the implementation of the decentralization policy, the people of the Sub-district of Pante Makassar also take advantage of the results of the implementation of the decentralization policy, but in evaluating the policy, the community does not participate in evaluating the policies that have been implemented.